The effects of cow manure vermicompost and municipal solid waste compost on peppermint (Mentha piperita L.) in Torbat-e-Jam and Rasht regions of Iran - Hossein Ayyobi; Jamal-Ali Olfati; Gholam-Ali Peyvast (International Journal of Recycling of Organic Waste in Agriculture)
Background The utilization of organic fertilizer is an effective method in organic culture of medicinal plants because of its beneficial effects on soil structure, reduction of environmental problem and improvement in plant growth. The experiments were conducted in a research field at the University of Guilan at the Rasht and Torbat-e-Jam Razavi Khorasan Province, Iran. The experiment was conducted to determine the effects of 7 Mt ha-1 of cow manure vermicompost, vermiwash prepared from 7 Mt ha-1 of vermicompost, leachate vermicompost ? vermiwash, 50 Mt ha-1 municipal solid waste compost (MSWC), chemical fertilizer (50, 0, 300 NPK) and no fertilization as a control on peppermint yield and quality. Results Organic fertilizers significantly affected all the measured characters except total phenols and antioxidant capacity compared to chemical fertilizers and the control. Plants treated with vermicompost, vermiwash or vermicompost leachate ? vermiwash were the tallest and had the highest levels of chlorophyll a, chlorophyll b, total chlorophyll and carotenoids. Plants treated with vermicompost had the highest essential oil yield (24.21 ml m-2 ). Plant growth in the Rasht region had the highest number of lateral branches (18), fresh (10.51 g) and dry weight (4.64 g) of plant, fresh (2,102.9 kg ha-1 ) and dry (928.67 kg ha-1 ) yield, leaf area index (0.17) and carotenoids (531.82 mg 100 g-1 ), while the highest oil per plant (0.24 ml plant-1 ) and oil yield (18.49 ml m-2 ), chlorophyll a (7.37 mg 100 g-1 ), b (4.07 mg 100 g-1 ) and total chlorophyll (11.44 mg 100 g-1 ), total phenol (7.48 mg gallic acid equivalent 100 g-1 ) and antioxidant capacity (71.89 (% of inhibition) were obtained from plants grown in the Torbat-e-Jam region. Conclusion Organic fertilizers beneficially affect soil structure and nutrient availability. The use of sustainable organic materials can increase fertility without negative effects on human health and environment. We counsel farmers to use leachate vermicompost and vermiwash in organic cultivation of peppermint separately or mixed together.